Analisis Keterlibatan Emosional Anak SD dalam Membaca Cerita Petualangan - Firda Mawaddatul Jannah; Muhammad Junaidi Retno Manggolo; Chovivah Nur Khaniv; Muhammad Nofan Zulfahmi (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Reading ability is a basic skill that every elementary school student must have, because through the reading process, children can learn various subjects better. The purpose of this study was to analyze the emotional involvement of elementary school students when reading adventure stories. Emotional involvement as a learning tool has been proven effective in increasing student interest and motivation, supporting the development of social and emotional skills, and improving critical and analytical thinking skills. The role of teachers and parents is very important in encouraging children's emotional involvement. Teachers can create a collaborative classroom environment, choose interesting books, and parents can set aside special time to read with their children at home. Teachers and parents need to work together to ensure that children get the support they need. This also has a significant impact on curriculum development, as interesting and relevant adventure stories are included in the curriculum to create a positive learning environment and encourage children's emotional involvement.